Return to Greatness : How America Lost Its Sense of Purpose and What It Needs to Do to Recover It - Wolfe, Alan, 1942- (Book collections on Project MUSE., 2005)
Has America, in its quest for goodness, sacrificed its sense of greatness? In this sharp-witted, historically informed book, veteran political observer Alan Wolfe argues that most Americans show greater concern with saving the country's soul than with making the nation great. Wolfe castigates both conservatives and liberals for opting for small-mindedness over greatness. Liberals, who at their best insisted on policies of national solidarity, have convinced themselves that small is beautiful, prefer multiculturalism to one nation, and are mistrustful of executive political power. Conservatives.